Resource Allocation In 5G and Beyond Networks for Mu-MIMO Systems - Eirini Barri; Christos Bouras; Apostolos Gkamas; Vasileios Kokkinos; Aspasia Koukouvela (The Twenty - First International Conference on Networks (ICN 2022), April 24 - 28, 2022, Barcelona, Spain, 2022)
The resource allocation problem focuses on finding an optimal allocation of a specific number of resources to maintain Quality of Service (QoS). That is where Multiple-Input Multiple-Output (MIMO) come in as a radio antenna technology. In order to, optimize data speed, minimize errors and improve the radio transmission capacity MIMO utilizes multiple antennas at both the transmitter and the receiver. This technology uses a variety of antennas and paths that carry the data. Each antenna uses different paths. Multi-user MIMO (mu-MIMO) stands for a technology that allows routers to communicate simultaneously with multiple endpoint devices and it is the next evolutionary step of single user MIMO. Over the past decade, significant advances have been made to improve the performance of mu-MIMO. Although non-negligible progress has been achieved so far, optimal algorithms for Resource Allocation (RA) will help better the performance of mu-MIMO by increasing the system’s performance in terms of throughput, fairness, and QoS. The purpose of this paper is to provide a comparison of different beamforming techniques used for resource allocation and list them in ascending order depending on their efficiency.